Risk Management for 4-H Youth Development Work: Insurance - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2010)
4H10.5, a 4-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It describes the necessity of accident and illness insurance and general liability insurance for the 4-H organization. Published by the Florida 4-H Youth Development Program, August 2010.